Perbedaan Tingkat Kecemasan Dental Terhadap Perawatan Gigi Pada Pasien Anak Umur 8 Dan 10 Tahun Di Puskesmas Banjar (Jurnal Terapi Gigi dan Mulut, 2023)
Dental anxiety is one of the things that must be considered because it will not only cause stress to the patient but also to the dentist when he is going to perform treatment. For pediatric patients, dental anxiety will have an impact on delaying treatment because children are afraid to come back to the dentist so that there is a decrease in oral health. The level of anxiety in children will be easy to observe at the age of 8-12 years because children aged 8-12 years are considered to already have the ability to recognize the environment and have a high curiosity. This study aims to determine differences in the level of dental anxiety in pediatric patients aged 8 and 10 years at the Banjar Health Center, Pandeglang Regency through interviews using a measuring instrument in the form of a CFSS-DS (Children's Fear Survey Schedule-Dental Subscale) questionnaire. The sample consisted of 30 respondents in each age group consisting of 15 children. Data analysis used independent t test. The results of the analysis: 73% of pediatric patients aged 8 years were in the category of not being anxious, with the highest level of anxiety in the “syringe” variable. 93% of the 10-year-old group were in the non-anxious category with the highest level of dental anxiety found in the "dentist" variable. Independent T Test showed the results of sig = 0.353> 0.05, so it can be concluded that there is no difference in the level of dental anxiety between children. ages 8 and 10 years.